2014
DOI: 10.1175/jamc-d-13-065.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Precipitation Increase with Urbanization in Tokyo as Revealed by Ensemble Climate Simulations

Abstract: This study examines how urbanization affects the precipitation climatology in Tokyo, Japan. A unique aspect of this study is that an ensemble, regional climatological simulation approach is used with sensitivity experiments to reduce uncertainty arising from nonlinearity in the precipitation simulations. Another aspect is that the robustness of the precipitation response is tested with ''stress response'' simulations with increasing urban forcing. The results show that urbanization causes a robust increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 44 publications
3
50
1
1
Order By: Relevance
“…The interactions of strong urban thermals with the natural topographic flow are analogously observed in inland and coastal cities (Freitas et al, ; Li et al, ; Miao et al, ; Ryu & Baik, ). As a result, the displacement or weakening/strengthening of these flows has significantly altered the rainfall patterns (Dixon & Mote, ; Kusaka et al, ; Thielen et al, ) and pollutant level within and around the city (Ji, Lee, & Lee, ; Thompson, Holt, & Pullen, ). The influence of urban thermals is further extended and complicated by the near proximity of urban to mountains and water body (Von Glasow et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of strong urban thermals with the natural topographic flow are analogously observed in inland and coastal cities (Freitas et al, ; Li et al, ; Miao et al, ; Ryu & Baik, ). As a result, the displacement or weakening/strengthening of these flows has significantly altered the rainfall patterns (Dixon & Mote, ; Kusaka et al, ; Thielen et al, ) and pollutant level within and around the city (Ji, Lee, & Lee, ; Thompson, Holt, & Pullen, ). The influence of urban thermals is further extended and complicated by the near proximity of urban to mountains and water body (Von Glasow et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its urban surfaces have often been argued to locally increase summertime precipitation (e.g., Fujibe et al 2009) as a result from an increase in low-level convergence over the city associated with enhancement of the Tokyo Bay breeze (e.g., Souma et al 2013, Kusaka et al 2014. In other meteorological situations the city has been shown to lead to the opposite effect, i.e., to a decrease in precipitation (i.e., Matheson and Ashie, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the most recent report on world urbanization prospects published by the United Nations indicated that in 2014, 54 % of the world's population resided in urban areas (http://esa.un.org/unpd/wup/ Highlights/WUP2014-Highlights.pdf); by 2050, the world's urban population is projected to be 66 %. Rapid urbanization has resulted in environmental problems including increasing energy consumption and air pollution, deterioration of visibility, a significant urban heat island (UHI) effect, urban heavy rainfall, and even local (regional) climate change (Oke, 1982;Grimmond and Oke, 1995;Atkinson, 2003;Arnfield, 2003;Jin et al, 2005;Feddema et al, 2005;Ren et al, 2007;Corburn, 2009;Kusaka et al, 2012bKusaka et al, , 2014Kang et Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%